INTERVENING AUDIT DELAY DALAM UKURAN DAN KOMPLEKSITAS PERUSAHAAN SERTA FINANCIAL DISTRESS PADA AUDITOR SWITCHING - Sitepu, Wilsa Road Betterment; Marlie, Andranic; Tantri, Jessica (2021)
The study intension is to search for the impact of size and complexity of a company and also financial distress on the auditor switching with audit delay as the intervening variable. The study use secondary data such as the yearly report financial statement from all infrastructure, utility, and transportation company that listed on the stock exchange website. This study use 75 company as the population. The effect of purposive sampling authors got 29 company that available because of the criteria that authors set. Logistic regression is the method authors use in analyzing the data and authors also use the path analysis on this study. Result of the test is company size does bring an impact to audit delay and auditor switching. On the other side Complexity and financial distress doesn’t bring any positive effect to audit delay or auditor switching. Authors find that audit delay as an intervening give an positive effect on auditor switching. The size of a company does indirectly gives an effect to the auditor switching from the intervention of audit delay. However the authors also fine that there is an direct effect comes from the complexity of a company and financial distress to the auditor switching from thr intervention of audit delay.